Cardiac and vascular effects of diltiazem, dobutamine and amrinone, drugs used after myocardial revascularization - Gómez Alvis, Alicia (2004)
Hemodynamic care during postoperative management of myocardial revascularization should include vasorelaxing drugs to insure adequate graft and coronary flow, and stimulation of stroke volume to maintain vascular perfusion pressure. We tested the cardiac (inotropic and lusitropic) and vascular (relaxant) effects of diltiazem (0.1 nM to 0.1 mM), dobutamine (10 μM to 10 mM) and amrinone (10 μM to 1 mM) on isolated rat atria and thoracic aorta, and also on isolated human saphenous vein (HSV) and human mammary artery (HMA). Dobutamine produced a maximal positive inotropic effect (+dF/dtmax = 29 ± 7%) at its ED50 for aortic relaxation (88 ± 7 μM). Conversely, at their ED50 for aortic relaxation diltiazem depressed myocardial contractility and amrinone did not exhibit myocardial effects. In HSV and HMA contracted with 80 mM potassium, diltiazem and dobutamine (but not amrinone) had a vasorelaxant activity similar to that in rat aorta. Norepinephrine-contracted human vessels were significantly more sensitive than potassium-contracted vessels to the relaxant effect of amrinone (ED50 HMA = 15 ± 5 μM, ED50 HSV = 72 ± 31 μM, P < 0.05). We conclude that at concentrations still devoid of myocardial effects dobutamine and amrinone are effective dilators in graft segment vessels and rat aorta contracted by membrane depolarization. If the difference between aortic and myocardial tissue still holds in human tissues, at the appropriate concentrations these drugs should be expected to improve cardiac performance while still contributing to the maintenance of graft patency.